THE MANAGEMENT SERVICE SYSTEM BUILDING EARTHQUAKE SENSOR EQUIPMENT (SiMPANSE) BASED ON INFORMATION TECHNOLOGY AT THE UPT LEVEL TO REALISE EXCELLENT EARTHQUAKE INFORMATION SERVICES - Septiadhi, Ardhianto; Widodo, Juniarto; Nugroho, Cahyo; Rahadi Prabowo, R Mulyono (Jurnal Widya Climago, 2023)
earthquake sources, monitoring seismic activity, disseminating information and increasing the community's response capacity to earthquake hazards. service is supported by reliable maintenance of earthquake observation equipment. equipment maintenance service for reliable earthquake observation. Geophysical Stations that in charge of maintaining observation equipment in its working area requires an equipment maintenance service that is able to identify sensor conditions that are not functioning properly for routine checks and maintenance routine checks and maintenance steps by UPT that are maintenance steps by UPT that are traceable, standardised and accountable from a technical and budgetary perspective. budget. This system can also monitor the UPT Service Level and budget absorption used for maintenance. UPT and budget absorption used for maintenance. In the development of excellent service also capacity building in understanding and responding to to earthquakes through measurable socialisation and simulation measurable socialisation and simulation, as well as building a shared commitment to to deal with earthquakes